Areal relations of Indo-European loanwords in Finnic dialects - Vilja Oja (Eesti ja Soome-ugri Keeleteaduse Ajakiri, 2014)
The areas of the distribution of Indo-European loanwords in Finnic dialects are described on many lexical maps of the Atlas Linguarum Fennicarum and the Atlas Linguarum Europae. The maps of those atlases offer an opportunity to follow the post-formational contacts of the languages. The analysis of the spread of loanwords makes it possible to find the main routes and centres of Indo-European innovations in Finnic dialects and discuss the reasons for the different sources of the influences. Sometimes, the Finnic area has been a boundary zone for several widespread Indo- European stems coming from different directions. Often the area distribution of dialect words is etymologically suggestive, but the source language depends on the concept. The differences in the use of stems with the same Indo-European origin in different Finnic languages may, at least partly, be due to the words having been borrowed at different times and from different donor languages.